Pós-verdade e segmentação algorítmica nas mídias digitais - Ilias, Sérgio Atieh (2021)
A clear definition of the phenomenon of post-truth is necessary when so many think it is just a different designation for lying, self-deception and opposition to the truth, so it is necessary to discuss what is different in our time from what was historically witnessed, and the the most significant change is represented by the algorithmic logic that segments content to users in a more easily verifiable way on social networks, mobilizing every way of life of a man set with quick, easy and ready-made truths based on a relationship adjacent to technology capable of legitimizing any expectation of true belief, prejudice or ideal. Based on the definition of terms central to this dissertation, it illustrates how post-truth is a phenomenon associated with the technological development of digital communications, based on the cartesian logic that seeks scientific and mathematical truths, but it is necessary to think that such an idea does not ignore aspects already seen aspects of a theoretical analysis focused in aspects of men's historical search for narratives that help them to understand their reality: deceiving others or being deceived by different interests presupposes investigating facts that are a constitutive part of the logic of the phenomenon. Having made such a digression, it was necessary to look into algorithmic logic and all its effects that empower a user inclined to embrace the easy discourse of post-truth, which led us to conclude that post-truth, unlike misleading news, lies, or selfdeceptions, it proves to be a more difficult and complex phenomenon to be combated than the fake news.